1956
DOI: 10.1146/annurev.ns.06.120156.001425
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Oxygen Isotopes in Chemical Studies

Abstract: The choice of the general subject of this article requires no apology, but the choice of the specific material to fit to the space allotted does. The limita tions and research interests of the reviewer were a governing factor in mak ing the selection, but also the consideration entered that the effects of the major omissions are tempered by other recent reviews in which much of the material omitted is discussed. Thus the important work in geochemistry involving oxygen isotopes is discussed in excellent reviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1959
1959
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 104 publications
(148 reference statements)
0
17
0
Order By: Relevance
“…Isotopic oxygen exchange between O2 and Hj 0 does not take place under our experimental conditions [14,15].…”
Section: O Exchangementioning
confidence: 68%
See 2 more Smart Citations
“…Isotopic oxygen exchange between O2 and Hj 0 does not take place under our experimental conditions [14,15].…”
Section: O Exchangementioning
confidence: 68%
“…The field has been reviewed many years ago; the report [15] still contains much of the pertinent information available to date. Almost invariably the oxygen exchange process was investigated using HjO enriched in "O.…”
Section: O Exchangementioning
confidence: 99%
See 1 more Smart Citation
“…2.5% inverse in the direction of formation of the metal hydrate. 46,47 Thus, understanding whether upstream equilibria are part of the reaction mechanism is crucial since they can have an important influence on the observed isotope effect.…”
Section: General Aspects Of Isotope Effect Measurement and Interpretamentioning
confidence: 99%
“…Oxygen-18 generally does not exchange between alcohols and water (10). However, only one author (11) has studied the system cellulose/water and a critical study of his data showed that less than 6% of the cellulose oxygens reacted.…”
Section: Introductionmentioning
confidence: 99%